The Effectiveness of Autogenic Training on Stress, Anxiety, and Quality of Life Among Elderly : A Systematic Review - Setya Rini, Puji (Sahabat Publikasi Kuu, 2026)
Introduction: Older adults are vulnerable to increased stress and anxiety due to physiological, psychosocial, and spiritual changes experienced with aging. These conditions negatively impact the quality of life (QoL). Autogenic Training (AT), a self-suggestion-based relaxation technique, is known to activate the body's relaxation response and reduce psychological tension. However, the effectiveness of AT on stress, anxiety, and quality of life in the elderly still requires comprehensive scientific evidence to be established. Methods: This study used a systematic review design based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Articles were searched for in the PubMed, ScienceDirect, and Google Scholar databases using the keywords: “Autogenic Training,” “Stress,” “Anxiety,” “Quality of Life,” and “Elderly.” Of the 287 articles identified, 48 were reviewed in full text, 12 met the methodological criteria, and 5 were not RCTs, were not experimental studies, and were not studies literature. Seven open-access articles (2020–2025) were included in the final analysis. Results: Seven studies showed consistent results that Autogenic Training is effective in reducing stress and anxiety and improving the quality of life of the elderly. Conclusion: Autogenic Training has been proven effective in reducing stress and anxiety and improving the quality of life of the elderly through physiological relaxation and psychological regulation mechanisms. This intervention is recommended as a non-pharmacological complementary therapy in gerontological nursing practice and forpromoting mental health in older adults.